2021
DOI: 10.1002/art.41800
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID‐19 in Rheumatoid Arthritis: A National Veterans Affairs Matched Cohort Study in At‐Risk Individuals

Abstract: Background While rheumatoid arthritis (RA) and its treatments are associated with an increased infection risk, it remains unclear whether these factors impact the risk or severity of COVID‐19. Methods We conducted a matched cohort study using national Veterans Affairs data. Among non‐deceased individuals on January 1, 2020 who received VA care in 2019, we matched RA to non‐RA patients (1:1) on age, sex, and VA site. COVID‐19 and severe COVID‐19 (hospitalization or death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
3
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 35 publications
7
122
3
8
Order By: Relevance
“…Our findings regarding immunosuppressive therapies extend the results of our earlier work and that of others examining the association between use of these medication classes and COVID-19 outcomes. In contrast to some studies that have suggested that people with immunosuppressive conditions are at increased risk of infection, 3 , 4 , 5 our finding of no increased risk of severe disease could be attributable to a combination of factors, including our focus on immunosuppressive medications rather than diagnoses, restriction to hospitalised patients with COVID-19, and analyses with statistical power and methods to address confounding and effect modification. By using a larger and more diverse cohort, our results add to a growing body of evidence suggesting the overall safety of several products in the context of continued COVID-19-related morbidity and mortality.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Our findings regarding immunosuppressive therapies extend the results of our earlier work and that of others examining the association between use of these medication classes and COVID-19 outcomes. In contrast to some studies that have suggested that people with immunosuppressive conditions are at increased risk of infection, 3 , 4 , 5 our finding of no increased risk of severe disease could be attributable to a combination of factors, including our focus on immunosuppressive medications rather than diagnoses, restriction to hospitalised patients with COVID-19, and analyses with statistical power and methods to address confounding and effect modification. By using a larger and more diverse cohort, our results add to a growing body of evidence suggesting the overall safety of several products in the context of continued COVID-19-related morbidity and mortality.…”
Section: Discussioncontrasting
confidence: 91%
“…However, previous studies have found that individuals with autoimmune diseases, such as rheumatoid arthritis or inflammatory bowel disease, have a greater incidence of COVID-19, but not of resultant invasive ventilation or death. 3 , 4 , 5 Case series of patients with solid organ transplant with SARS-CoV-2 infection have compared the risk of severe COVID-19 outcomes to that of the general population and found higher hospitalisation and case fatality rates in the initial months of the pandemic (March to June, 2020). 6 , 7 , 8 Despite the insights from these early studies, some questions remain unanswered, such as whether time trends in COVID-19 management could explain these apparent increased risks.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of men, two inflammatory conditions were associated with higher severity: rheumatoid arthritis (in line with what was observed in women) and polymyalgia. It has been reported that autoimmune diseases are not significantly associated with severe COVID-19 progression [49], and poor outcomes could simply be linked to older age and comorbidity [45], though one study did find a 39% increase in the adjusted risk of hospitalization and mortality in a sample of mostly male patients with COVID-19 infection and rheumatoid arthritis [50]. In women, we found a high risk of severe COVID-19 outcomes in patients with HIV infection and, although similar findings have been published in the literature, further studies are needed to better assess this risk taking into account disease control, treatment, analytical blood parameters, and comorbidity [51][52][53].…”
Section: Plos Onementioning
confidence: 99%
“…IJD compared with the general population. [1][2][3][4] Most of these studies are based on data from the first 'wave' of the COVID-19 pandemic. The second wave was more penetrating in terms of number of confirmed cases and deaths, but also came with improved in-hospital care including the use of corticosteroids and optimised use of oxygen, which may have affected case fatality.…”
Section: Key Messagesmentioning
confidence: 99%